Measuring enhanced weathering: inorganic carbon-based approaches may be required to complement cation-based approaches - Hasemer, Heath; Borevitz, Justin; Buss, Wolfram (Frontiers in Climate, 2024)
The removal of atmospheric carbon dioxide (CO2) is now essential to meet net zero goals and limit the impacts of climate change. Enhanced weathering is a method of sequestering CO2 that involves the distribution of finely ground silicate rocks over agricultural land. The weathering of these silicate rocks releases cations into solution which can balance dissolved inorganic carbon, effectively removing CO2 from the atmosphere. Despite being a promising method of carbon dioxide removal (CDR), enhanced weathering has been limited by uncertainty surrounding the measurement of CO2 sequestration. This study compares current measurement approaches that focus on quantifying inorganic carbon and cations within the soil and leachate. Cation-based calculations of CDR were compared to inorganic carbon-based calculations of CDR and soil results were compared to leachate results. The recovery rate of cations in the soil fraction was also tested. Three different ground silicate minerals/rocks – basalt, olivine and wollastonite, were mixed with two different soils and were allowed to weather over 16 weeks in 320 pots with and without plants under different watering regimes and the application of an acidifying fertiliser. Soil and leachate samples were analysed for cations by ICP-OES and inorganic carbon by direct CO2 analysis after acidification and total alkalinity titration (in leachate only). The results indicate that the soil retains most enhanced weathering products through the cation exchange reactions. CDR estimated by cations is often greater than CDR estimated by inorganic carbon. Measurement approaches to estimate cations are susceptible to incomplete or improper accounting through the under-extraction of cations stored within the soil-exchangeable pool, the activity of non-carbonic acids and CO2 outgassing. Inorganic carbon-based measurements, including direct inorganic carbon and total alkalinity analysis, are also complicated by the potential for CO2 loss through carbonate precipitation and re-equilibration. Therefore, inorganic carbon-based approaches and cation-based approaches should be reconciled to validate the estimation of CDR. The inorganic carbon-based estimation of CDR in leachate should equal the cation-based estimation of CDR in leachate—which will be achieved after quantification or estimation of the natural mechanisms that affect each approach. These findings will support the development of accurate measurement processes for enhanced weathering.